EMPLOYMENT OF VILLAGERS EFFECTIVE SOCIAL PROVISION MECHANISMS (World Economics and Finance Bulletin, 2023)
The article analyzes the effective social mechanisms of employment of the rural population in the service sector and provides conclusions and recommendations
Keywords: employment; macroeconomics; market infrastructure; urbanization